Impact of supply chain actor citizenship behavior on supply chain learning processes - H. L. Liyanage (Kelaniya Journal of Management, 2018)
Critical evaluation of early literature into supply chain learning indicates lack of research into the impact of supply chain actor citizenship behavior on supply chain learning processes. Therefore, this study explores the impact of supply chain actor citizenship behavior impact on supply chain learning processes. The study uses constructivist epistemology, interpretative theoretical perspective, case study research methodology and grounded theory thematic technique in data analysis. Findings of the study indicate that different elements of the supply chain actor citizenship behavior concept are connected to different levels of supply chain learning processes. Self-development is found to have an impact on intuition process, helping behavior is found to have an impact on interpretation process, tolerance is found to have an impact on integration process and constructiveness is found to have an impact on institutionalization process. An original contribution to theory includes extending organizational learning theory and citizenship behavior concept to supply chain context. And practitioners are recommended to explore dynamics of self-development, helping behavior, tolerance, and constructiveness on enhancing supply chain learning processes.